Penerapan Keterampilan 4C (Critical Thinking, Creativity, Collaboration, Communication) Dalam Pembelajaran Abad 21 di Sekolah Dasar - Taufiqulloh Dahlan; Wanti Nurasiah; Intan Lestari Nur Inayah; Fadillah Azkia; Aulia Dwi Ardhiana; Aida Zahwa; Atiya Nashwa Raushani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The implementation of 4C skills (Critical Thinking, Creativity, Collaboration, and Communication) is the main key to realizing 21st-century learning that is relevant to global demands. This study aims to describe the strategy for implementing 4C in elementary schools and analyze its impact on student engagement and learning outcomes. The study used a qualitative descriptive approach with exploratory study techniques on various literature and implementation practices in elementary schools. The results of the study indicate that 4C skills can be developed effectively through active learning models such as Project Based Learning (PjBL), Problem Based Learning (PBL), and Collaborative Learning. Teachers play a crucial role as facilitators, innovators, and motivators who create contextual and meaningful learning experiences. A school environment that supports collaboration, creativity, and communication is an external factor determining success. The positive impact of 4C implementation is seen in improving students' critical thinking skills, creativity, cooperation, and self-confidence. However, teachers still face obstacles such as limited time, facilities, and pedagogical competence. Therefore, it is necessary to strengthen teacher capacity through training, support from school facilities, and collaboration with parents to create an adaptive and sustainable learning ecosystem. Overall, implementing the 4Cs is an essential strategy for developing a young generation that is critically thinker, creative, communicative, and able to collaborate in facing the dynamics of the 21st century.